The establishment of the Sea Turtle Conservation and Marine Pearl Educational Tourism Website in Sumbreng aims to promote ecosystem balance. - Devina Puspita Sari; Galih Anindita; Edy Setiawan; Aminatus Sa'diyah; Purwidi Asri; Ni'matut Tamimah; Ii Munadhif; Ponti Almas Karamina; Syafiuddin; Anggara Trisna Nugraha; Suci Indaryani; Mukhammad Jamaludin; Muhammad Bilhaq Ashlah; Muhammad Izzul Haj; Diego Ilham Yoga Agna; Salsabila Ika Yuniza; Faris Riyadi; Fajar Rahmat Adzani; Andika Aldo Pratama; Rahmania Firdiansyah; Laili Agustin Widyaningrum (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The coast is an area that has potential for tourist attractions, including for turtle conservation which is relied on as a support for the economy. Turtles are one of the protected animals, not just protected by law because they are feared they will become extinct. The Turtle Conservation